Relationships of Osmolality and Oxidative Stress with Semen Quality and Their Effects on Male Fertility - Ameen, Edrees Mohammad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
The objective of this study was to investigate and find the relationships between human semen osmolality and oxidative stress with semen quality. Semen analysis was determined to evaluate semen quality and fertility. The concentration of semen malondialdehyde (MDA) was measured to assess oxidative stress. For this purpose, one hundred seventy healthy adult males were used in this study. The study was conducted from September 2018 to November 2019 in the Infertility care and in vitro fertilization center (IVF) and the Biology department of the College of Science at Salahaddin University in Erbil city. A significant positive correlation was observed between the total sperm motility, grade activity, and sperm motility index with semen osmolality less than 300 mOsm kg-1 (r= 0.62, r = 0.64, and r= 0.75 p≤0.01 respectively) and osmolality 300-350 (r= 0.53, p≤0.05 r= 0.52 p≤0.05, and r= 0.56 p≤0.01 respectively). Total sperm motility, grade activity, and sperm motility index are negatively correlated with osmolality 351-400 mOsm kg-1 (r= -0.65 p≤0.05, r= -0.56 p≤0.05, and r= -0.67 p≤0.01) and more than 400 mOsm kg-1 (r= -0.86, r = -0.74 and r= -0.88 p≤0.01). Regarding the relation between oxidative stress and sperm motility kinetics, total sperm motility, grade activity, and sperm motility index is negatively correlated with MDA more than 2 µmol/L (r= -0.56 p≤0.05, r= -0.52 p≤0.05, and r= -0.67 p≤0.01 respectively). No significant correlation was found between semen osmolality and MDA concentration with sperm concentration, total sperm count, sperm viability, and normal sperm morphology.